Enhancing the Pupils' Speaking Abilities through Debate - Erfina Maulidah Khabib; Suci Muliana; Paulina Deby Putri Indrawati (Universitas Islam Negeri Palopo, 2025)
This study aims to examine the effectiveness of the debate method in enhancing students' English-speaking abilities while also exploring its impact on pupils, its influence on soft skills such as collaboration and empathy, and identifying the optimal duration and frequency of debate activities for maximum educational benefit. The research was conducted using a classroom action research design implemented in two cycles. Data were gathered through speaking tests, classroom observations, and pupils’ interviews. The results demonstrate significant improvements in students’ speaking performance. Specifically, pronunciation improved by 51.16%, vocabulary by 50%, fluency by 72.5%, grammar by 87.88%, and comprehension by 89.19%. These findings suggest that integrating debate into speaking instruction is an effective pedagogical approach that enhances students’ English-speaking proficiency.